2007
DOI: 10.2466/pms.104.3.1297-1309
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Upper Limb Proprioceptive Acuity

Abstract: Although upper limb movements are known to be slower and more variable in elderly persons, the extent to which these changes are associated with deficits in movement-related sensory feedback is poorly understood, despite the importance of proprioception in the control of skilled movement. Age-related changes were examined with 22 participants (10 of M age 27 years and 12 of M age 75 years) in performance of an elbow position-matching task which varied in terms of interhemispheric transfer and/or the need to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
72
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(84 citation statements)
references
References 0 publications
10
72
2
Order By: Relevance
“…Overall, these results are strongly in line with the current field of knowledge on proprioceptive acuity in older age. Specifically, several other investigators have reported an age-related decline in motion (Kokmen et al 1978;Wright et al 2011) and position sense of the upper limbs (Adamo et al 2007;Adamo et al 2009;Herter et al 2014). These deteriorations may partially be caused by physiological changes in the structure and function of muscle spindles throughout late adulthood (Herter et al 2014;Kalisch et al 2012;Proske and Gandevia 2012).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Overall, these results are strongly in line with the current field of knowledge on proprioceptive acuity in older age. Specifically, several other investigators have reported an age-related decline in motion (Kokmen et al 1978;Wright et al 2011) and position sense of the upper limbs (Adamo et al 2007;Adamo et al 2009;Herter et al 2014). These deteriorations may partially be caused by physiological changes in the structure and function of muscle spindles throughout late adulthood (Herter et al 2014;Kalisch et al 2012;Proske and Gandevia 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, there was no evidence to show that the withdrawal of visual feedback increased aiming errors in the non-active older adults more than in the other three groups, even though the proprioceptive ability of this group was, generally, inferior (negating hypothesis 3). Those seemingly contradicting outcomes require further attention because main body of findings from both experiments are consisted with a vast body of literature on effects of physical activity and aging on manual aiming (e.g., Chaput and Proteau 1996;Lyons et al 1996;Seidler-Dobrin and Stelmach 1998;Van Halewyck et al 2014) and proprioception (e.g., Adamo et al 2007;Adamo et al 2009;Herter et al 2014;Wright et al 2011). The specific effects of age and physical activity level on manual aiming and proprioception as emerged in findings of experiment 1 and experiment 2 are discussed in more details next.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adaptation of a method classically used to test the proprioceptive perception could remove the aforementioned limits in internal models assessment: the contralateral concurrent joint position matching task (Adamo et al 2007;Goble and Brown 2007). In this task, a subject's limb is displaced to a reference position.…”
Section: Introductionmentioning
confidence: 99%